2011
DOI: 10.1007/s12529-011-9201-6
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Mental Health Effects: A Population-Based Study among Married Women in Karachi, Pakistan

Abstract: The findings in this study highlight that the violence women have to face contributes to the development of multiple forms of psychological stress and serious mental health problems. Women's restrictive life circumstances seriously hamper women's empowerment. Reliable health surveillance system and health care services are needed to serve abused women. Policy initiatives focused on IPV and gender inequality in Pakistan should be initiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 33 publications
12
80
0
Order By: Relevance
“…Slapping and pushing were the most commonly reported forms of physical abuse (Fikree & Bhatti, 1999).The prevalence of physical IPV was reported in 20 studies (Ali et al, 2009;Ali et al, 2005;Ali, Asad et al, 2011;Ali, Mogren et al, 2011;Asif et al, 2010;Farid et al, 2008;Fikree & Bhatti, 1999;Fikree et al, 2006;Fikree et al, 2005;Kapadia et al, 2010;Karmaliani et al, 2008;Niaz et al, 2002;Rabbani et al, 2008;Shaikh, 2000Shaikh, , 2003Shaikh et al, 2008;Zareen et al, 2009). The lifetime prevalence of physical IPV, defined as experiencing physical IPV at least once during the marital period, ranged from 16%-80% with the six studies reporting a life time prevalence of physical IPV between 28%-35% Farid et al, 2008;Fikree & Bhatti, 1999;Fikree et al, 2004;Niaz et al, 2002;Shaikh, 2000).…”
Section: Physical Ipvmentioning
confidence: 99%
See 1 more Smart Citation
“…Slapping and pushing were the most commonly reported forms of physical abuse (Fikree & Bhatti, 1999).The prevalence of physical IPV was reported in 20 studies (Ali et al, 2009;Ali et al, 2005;Ali, Asad et al, 2011;Ali, Mogren et al, 2011;Asif et al, 2010;Farid et al, 2008;Fikree & Bhatti, 1999;Fikree et al, 2006;Fikree et al, 2005;Kapadia et al, 2010;Karmaliani et al, 2008;Niaz et al, 2002;Rabbani et al, 2008;Shaikh, 2000Shaikh, , 2003Shaikh et al, 2008;Zareen et al, 2009). The lifetime prevalence of physical IPV, defined as experiencing physical IPV at least once during the marital period, ranged from 16%-80% with the six studies reporting a life time prevalence of physical IPV between 28%-35% Farid et al, 2008;Fikree & Bhatti, 1999;Fikree et al, 2004;Niaz et al, 2002;Shaikh, 2000).…”
Section: Physical Ipvmentioning
confidence: 99%
“…It is usually celebrated on or around 12 th Rabi' al-awwal, and on the occasion processions are held, homes or mosques are decorated, charity and food is distributed, stories about the life of Muhammad are narrated, dhikr and Durood -o-salam are recited 2 A Majlis is a program of speeches on various issue from religious perspective (usually at a mosque) such as a friend or a neighbor. In addition, the number of women who disclosed their experience to the police, the local council or a health care professional was negligible (Ali, Mogren et al, 2011;. "The women perceived formal institutions to be unsympathetic, uncaring, and bureaucratic" (Zakar et al, 2011, p. 77).…”
Section: Victim's Response To Ipv In Pakistanmentioning
confidence: 99%
“…15 Other studies conducted in Pakistan observed multiple forms of violence that Pakistani women face which cumulatively contribute to the development or continuation of different forms of psychological stress and serious mental ill health. 16 In the present study it was found that 52.05% (n=38) of females that had experienced physical violence have sought for help. Abused women most often sought help from their families (n=30, 78.9%) and only 13% (n=5) sought help from husband's family.…”
Section: Association With Socio-demographic Factorsmentioning
confidence: 51%
“…These findings point to serious violations of women's rights and require the immediate attention of health professionals and policymakers. [3][4][5][6][7][14][15][16][17][18][19] …”
Section: Association With Socio-demographic Factorsmentioning
confidence: 99%
“…Supporting these claims, Ali, Mogren and Krantz found that the prevalence of poor mental health was considerably higher in Pakistani women exposed to any form of violence, as compared with unexposed women. Suicidal thoughts were reported by 65% -74% of women exposed to physical, sexual or psychological violence [23]. Similarly, another study showed that depression in married women in Pakistan was strongly associated with domestic abuse by in-laws (OR 4.91; 95% CI = 2.66, 9.06) and marital rape (OR 3.03; 95% CI = 1.50, 6.11) when compared with a control group [24].…”
Section: Discussionmentioning
confidence: 98%